PENGEMBANGAN DESA WISATA DI BALI MELALUI PENGUATAN LEMBAGA PERKREDITAN DESA (LPD) BERLANDASKAN ATAS TRI HITA KARANA - Ida Ayu Putu Sri Astiti Padmawati, SH.,MH. (VYAVAHARA DUTA, 2025)
This study aims to reconstruct the LPD as a village-owned financial institution that can play a role in the development and formation of tourist villages in Bali. The research method used in this study is normative method. The research used statute, conceptual, and sociological approach. The existence of tourism village in Bali provides space for LPDs to participate in making their presence knowns amidst increasingly fierce competition between banking institutions. LPD is the main milestone of local wisdom-based capital in the development of tourist village in Bali. Of course, LPD institutions need to cooperate with other local institutions, including Village -Owned Enterprises. This research proves the relevance of Cybernetics theory, which is tailored to the role of the LPD as a traditional village financial institution. This research offers institutional strengthening of LPDs in the development of Tourism Villages in Bali through a cooperation scheme with Village-Owned Enterprises as a village-owned legal entity that can carry out business activities.